PENGARUH MOTIVASI KERJA,SETRES KERJA DAN KEPUASAN KERJA TERHADAP KOMITMEN KERJA KARYAWAN CV.MAHA SURYA MOTOR SINGARAJA - Nyoman Sulasmi; Mertyani Sari Dewi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
The purpose of this study was to determine the effect of Work Motivation, Job Stress, and Job Satisfaction on Employee Work Commitment CV. Maha Surya Motor Singaraja. In this study using a quantitative approach. Data collection techniques in this study used a questionnaire with a Likert scale. The number of samples used in this study were 69 employees which were the total number of employees from three branches of Maha Surya Motor (Maha Surya Motor; Penarukan, Singararaja, and Seririt) and the sampling technique used the total sampling method. The data analysis technique used in this study is SPSS version 25.0. The regression analysis method used to test the hypothesis was the f test and t test at a 95% confidence level = 0.05. The results of the first hypothesis were said to be significant positive with a significance value of 0.041 <0 .05. Likewise, the second hypothesis is said to be significant positive with a significance value of 0.036 <0.05. And the third hypothesis is said to be significant with a significance value of 0.000 <0.05.